Sukaramai Traditional Market Condition from the Users’ Perspectives - Marisa, Amy; Siregar, Rahma Wardani (International Journal of Architecture and Urbanism, 2026)
Sukaramai traditional market is one of the markets located in Medan which was rebuilt by the government after the fire incident in 2010 to improve the quality of the traditional market condition. Therefore, it is important to analyze the condition of Sukaramai traditional market, whether or not it has accommodated the need of the market users. This study aims to analyze the condition of Sukaramai traditional market based on the perceptive of its users. This study employs a quantitative approach using a questionnaire survey as a method for data collection. The analysis in this study includes frequency and descriptive analysis. The results show that the condition of Sukaramai traditional market is still insufficient according to the perspective of its users, with a total mean score of 3.01.This is mainly due to the circulation condition as well as inadequate facilities and infrastructure in the Sukaramai traditional market. This research can be useful as a valuable feedback for the traditional market management, planners and the government in planning traditional markets that are able to meet the needs of their users.